Identifikasi bakat olahraga di kalangan anak-anak di Malang - Hariadi, Imam; Hanief, Yulingga Nanda; Fadhli, Nurrul Riyad (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Talent Identification is essential to identify the potential of young athletes to succeed in senior elite sports. This study aimed to identify talent in sports among children in Malang. This research was an observational cross-sectional study involving 356 children (68% boys) who were purposively selected in Malang city based on age criteria (age 11 years old). Several tests and measurements were conducted for talent identification, including anthropometric tests, eye-hand coordination, leg muscle power, arm muscle power, agility, speed, and VO2max. Sports talent identification was conducted based on Norm developed by Narlan and Juniar. The results were matched into a sports talent profile table according to the age and gender of the participants. Results with the sports branch profile norms were matched, if the test results were at least the same or better than the sports study program, then the child was "talented" in that sport. The results of data analysis showed that two children (0.56%) were in the potential category, 58 children (16.29%) were in the moderately potential category, 172 children (48.31%) were in the low potential category, and 124 children (34.83 %) were included in the non-potential category. Judo, triple jump, long jump, high jump, javelin throw, table tennis, and shot put were sports identified as gifted by children in the categories of potential, moderate, and low potential. The results of the study report that children have the potential to be able to excel in Judo, triple jump, long jump, high jump, javelin throw, table tennis, and shot put.